Induction of the SOS response in Escherichia coli inhibits Tn5 and IS50 transposition. - Weinreich, M D (1991)
In response to DNA damage or the inhibition of normal DNA replication in Escherichia coli, a set of some 20 unlinked operons is induced through the RecA-mediated cleavage of the LexA repressor. We examined the effect of this SOS response on the transposition of Tn5 and determined that the frequency of transposition is reduced 5- to 10-fold in cells that constitutively express SOS functions, e.g., lexA(Def) strains. Furthermore, this inhibition is independent of recA function, is fully reversed by a wild-type copy of lexA, and is not caused by an alteration in the levels of the Tn5 transposase or inhibitor proteins. We isolated insertion mutations in a lexA(Def) background that reverse this transposition defect; all of these mapped to a new locus near 23 min on the E. coli chromosome.